ALK or ROS1-rearranged breast metastasis from lung adenocarcinoma: a report of 2 cases. Issue 6 (December 2019) - Wu, Xiao; Wang, Hong; Fang, Mei; Li, Chun; Zeng, Yun; Wang, Kai
Background: Breast metastases from extramammary sites are extremely rare, with an incidence of 0.4%–1.3% reported in the literature. Insufficient knowledge about its pathology and genetic mutation often leads to misdiagnosis and delayed treatment. Case presentation: We present 2 patients with synchronous (case 1) or metachronous (case 2) breast nodules, revealed as atypical breast metastases from pulmonary adenocarcinomas, in which ALK or ROS1 rearrangement were finally detected in breast mass. After they failed sequential treatments with standard chemotherapies for lung and breast cancer, we reexamined breast lump biopsy and found they were all lung adenocarcinoma metastasis to the breast with the presence of an ALK rearrangement in one case and of ROS1 rearrangement in the other. Eventually these 2 patients were treated with crizotinib. Both the primary tumor and the metastasis of these 2 patients were significantly regressed. Conclusion: Whenever a diagnosis of a suspected tumor with sites at more than one organ is made, pathologic as well molecular pathologic examinations designated for organ-specific cancers should be done.